PENINGKATAN PENGETAHUAN TENTANG HEALTHY EATHING INDEX UNTUK PENCEGAHAN DIABETES MELLITUS - Hariati, Hariati; Sitorus, Friska Ernita; Girsang, Rostiodertina; Barus, Dewi Tiansa; Zuliawati, Zuliawati; Purba, Rentawati; Sembiring, Alprindo (INSTITUT KESEHATAN DELI HUSADA, 2023)
Diabetes Mellitus is a disease that cannot be cured but can be controlled. To control diabetes mellitus requires knowledge and abilities from the community. In connection with the high incidence of diabetes mellitus in hamlet IV Sidodadi Village, it is necessary to carry out outreach activities regarding Increasing Knowledge about the Healthy Eating Index to Prevent Diabetes Mellitus. The foods that can be consumed at home as a way to prevent Diabetes Mellitus are foods made from whole grains or complex carbohydrates such as brown rice, baked potatoes, oatmeal, whole grain bread and cereals, replacing sugar with low-fat sweeteners. calories, lean meat steamed, boiled, grilled and grilled, vegetables processed by boiling, steaming, grilling or consumed raw, fresh fruit, nuts, including soybeans in the form of steamed, cooked tofu for soups and stir-fries, low-fat dairy products and eggs, fish such as tuna, salmon, sardines and mackerel, if you adopt a healthy diet, your body weight will remain ideal, blood sugar levels will be stable, and you will avoid the risk of heart disease. The benefit of carrying out this service activity is that the residents of Dusun IV, Sidodadi Village understand more about diabetes mellitus properly and development in the health sector, especially the health of the elderly, improves as this activity is held.